Regulator flexibility and the administrative allocation licensing of 3G spectrum - Madden, Gary; Morey, Aaron (Taylor & Francis, 2013)
Globally, most nations assign radio spectrum to provide 3G mobile services during the period 1999-2007. While there is consensus among most economists that auctions are the preferred assignment mechanism, the assignment mode is split, more or less, equally (in terms of the number of licences issued) between administrative allocations and auctions. With auction procedures tending to raise more revenue for governments (Cartelier, 2003) the question that naturally arises is: why are administrative allocations so popular a method to assign spectrum? McMillan (1995) conjectures that administative allocations provide additional 'flexibility'. Accordingly, this study examines the performance of 3G assignments in terms of econometric analysis of a unique sample of national 3G spectrum administrative allocations. These outcomes are modelled as depending on spectrum package attributes, and post-award network development requirements.